CRYPTOSYSTEM FROM MULTIPLE BIOMETRIC MODALITIES - Haitham Wahdan; Abdel-Moneim Wahdan; Aliaa A. A. Youssif (European Scientific Journal, ESJ, 2013)
One of the most important parts of cryptographic systems is key generation. Researchers, for a long time period, have been inventing ways to produce tough and repeatable cryptographic keys. Keys that had these features are hard to be memorized and may be stolen or lost. For this purpose using biometric features to generate cryptographic key is the best way. Most previous Researchers focused to extract features and generate key from an individual biometric, but it is hard to be used in multi stages cryptographic systems. Therefore, this approach is enhancing the cryptographic systems by using long and complex cryptographic keys that are hard to be guessed and do not need to be memorized and provide better usage in multi stages cryptographic systems by extracting features from multi biometrics, That provides accuracy 99.83% with time less than using individual biometric by 90%.